Licensed to Kill - Dong, Arthur (United States, 1997)
A journey into the minds of men whose contempt for homosexuals led them to murder. Attacked in 1977 by gay bashers on the streets of San Francisco, filmmaker Arthur Dong confronts murderers of gay men face-to-face in his film. The documentary is an uncompromising investigation into the roots of anti-gay violence through the eyes of murderers. It examines the social, political and cultural environments of these men and questions whether society had given them a "license to kill" homosexuals.
Soros Documetary Fund
Duration: 01:20:00
Soros Documentary Fund